(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Entry. For normal growth and development of crops, it is not enough to meet their basic needs for nitrogen, phosphorus, potassium, calcium, magnesium and sulfur. Trace elements in plant nutrition play no less important role than all of the above. The main importance of trace elements is to increase the activity of enzymes. Enzymes are biological catalysts that accelerate chemical processes in the body, which increases the overall tone of the plant, and has a positive effect on the dynamics of growth and development. The system of plant nutrition with trace elements should be developed individually for each crop, taking into account the peculiarities of the geographical location and the level of removal of trace elements by the plant. Analysis of the latest research and publications. Creating the concept of the nutrient cycle, D.M. Pryanishnikov emphasized that it is necessary to fertilize the plant, not the fields. Ignoring this statement leads to both a decrease in productivity and an increase in capital investment. One of the ways to solve the problem of environmentally safe farming is the use of humic preparations produced on the basis of natural soil components. Due to their unique properties, natural humic substances increase the energy of the plant cell, stimulate vital processes, improve the physicochemical properties of the soil, activate the activity of microorganisms, and enhance the beneficial effect of other substances The use of humic preparations in the technologies of growing crops contributes to better growth and development of plants, increasing their resistance to infectious diseases, adverse environmental factors environment, yield growth. Materials and methods. The experimental plots were laid in APO "Mriya" LLC in the Bohodukhiv district of the Kharkiv region. Growth stimulants (fertilizers) manufactured by Pesticide EOOD (Bulgaria) were used for the research: Zinoviy Triple Extra Force, Zinoviy Triple Korn, Zinoviy Triple Oil, Zinoviy Triple Double, Zinoviy Triple Green, Zinoviy Triple, Zinoviy Grand Gury. Research results and discussion. The use of Zinoviy group preparations for foliar feeding has a positive effect. In our opinion, these preparations, in addition to ensuring the supply of certain nutrients, contribute to a certain reduction in the temperature stress of climatic conditions on the oat plant. Foliar feeding with test preparations contributes to better fertilization of grains. With a single (2 l/ha) use of preparations, the increase in the number of productive kernels averaged 0.3 – 1.3 pcs per plant. Preparations such as Zinoviy Triple Korn, Zinoviy Triple Oil and Zinoviy Triple Extra Force had a particularly positive effect on the number of productive grains. With two doses (2+2 l/ha) of the preparations, a higher number of productive grains was also observed for these preparations, and with the same increase in the amount. When using foliar fertilization with the studied preparations at a dose of 2 l/ha, the highest yield increase was recorded for Zinoviy Triple Corn (1.05 t/ha, or 47.3% relative to the control), Zinoviy Triple Oil (0.99 t/ha, or 44.6% relative to the control) and Zinoviy Triple Extra Force (0.59 t/ha, or 26.6% relative to the control). When using foliar fertilization with the studied preparations at a dose of 2+2 l/ha, the highest yield increase was recorded for Zinoviy Triple Corn (1.08 t/ha, or 48.6% relative to the control), Zinoviy Triple Oil (1.05 t/ha, or 47.3% relative to the control) and Zinoviy Triple Extra Force (0.99 t/ha, or 44.6% relative to the control). A higher increase in yield is recorded with a single foliar feeding with the studied preparations. If with a single use of Zinoviy Triple Corn the increase in yield is 1.05 t/ha, then with a double use it increases by only 0.03 t/ha, respectively for Zinoviy Triple Oil preparations – by 0.06 t/ha, Zinoviy Triple Extra Force – by 0.40 t/ha. Conclusion. Studies have shown that the oat culture turned out to be quite sensitive to foliar feeding with the studied preparations. This manifested itself in a higher vegetative mass of plants and the number of productive kernels, which led to an increase in the yield of oats.